Consumer-Based Brand Equity in the Television Industry: A Study of A Local Television Channel in Yogyakarta (The Case of ADiTV) - , ERDILIA ADRIASARI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The new technological development and lower entry barriers into the media industry have led to higher competition, especially in television channel industry. Consequently, the television networks have to find ways of building distinctive and meaningful brand in the minds of news audiences also the strong brand equity in order to be able to capture more audiences and compete with competitors. Therefore, this research examines the consumer-based brand equity (CBBE) of a local television channel, ADiTV, in Yogyakarta. The purpose of this research is understanding the effect of each brand equity dimension to ADiTVâs brand equity. Those dimensions are brand awareness, perceived quality, brand loyalty, brand image, brand association, and organizational association. This research was conducted to 180 audiences of ADiTV in Yogyakarta using online and offline questionnaires. Then, the data were analyzed by multiple regression analysis. The result is all of the dimensions of brand equity give significant positive effect in ADiTVâs brand equity except brand loyalty. However, perceived quality is the dimension that gives the strongest significant positive effect on ADiTVâs brand equity.